BMO estimate to A-harmonic systems with discontinuous coefficients. (December 2015) - Yu, Haiyan; Zheng, Shenzhou
Abstract: In this note, we prove a global BMO estimate of the gradient of each weak solution to a class of nonlinear degenerate elliptic system with leading coefficients satisfying vanishing means oscillations. This conclusion perfects nonlinear Calderón–Zygmund theory in the limiting case to certain degenerate elliptic system. As an application of the BMO estimate, we give another proof to its L p theory with 1 < p < ∞ to linear elliptic system with VMO leading coefficients by Stampacchia's interpolation and duality.